2020
DOI: 10.3390/nu12051208
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Vitamin K and Osteoarthritis: A Review of Current Evidence

Abstract: Vitamin K is a cofactor of γ-glutamyl carboxylase, which plays an important role in the activation of γ-carboxyglutamate (gla)-containing proteins that negatively regulate calcification. Thus, vitamin K status might be associated with osteoarthritis (OA), in which cartilage calcification plays a role in the pathogenesis of the disease. This review collates the evidence on the relationship between vitamin K status (circulating or dietary intake level of vitamin K, or circulating uncarboxylated gla proteins) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Since VKDPs, including MGP, Gla-rich protein (GRP), periostin, and OC, were detected in cartilage and bone, VK may have a protective role in OA and joint health [79]. Thus, sufficient dietary VK intake and/or supplementation seemed to protect the population from age-related musculoskeletal diseases [80].…”
Section: Vitamin K In Bone Healthmentioning
confidence: 99%
“…Since VKDPs, including MGP, Gla-rich protein (GRP), periostin, and OC, were detected in cartilage and bone, VK may have a protective role in OA and joint health [79]. Thus, sufficient dietary VK intake and/or supplementation seemed to protect the population from age-related musculoskeletal diseases [80].…”
Section: Vitamin K In Bone Healthmentioning
confidence: 99%
“…Later vitamin K uptake was shown to be inversely related to bone fracture and osteoporosis risk and vitamin K has been demonstrated to promote bone formation and suppress bone resorption [19,37,38]. Moreover, Vitamin K has also been associated with osteoarthritis and rheumatoid arthritis [39][40][41][42].…”
Section: Vitamin K In Skeletal Development and Diseasementioning
confidence: 99%
“…Vitamin K has been shown to ameliorate experimental arthritis in the rat. This effect has been suggested to be mediated by vitamin-K-dependent inhibition of synovial hyperplasia and is considered to be independent of VDKPs [41]. In inflammatory arthritis synovial fibroblast-like cells (SFLCs) exhibit increased proliferation and less apoptosis in response to inflammatory signals.…”
Section: Vdkp-independent Effects Of Vitamin K On Skeletal Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…As such, low vitamin K levels have been hypothesized to play a role in OA pathogenesis (14,15). Similarly, J o u r n a l P r e -p r o o f vitamin K antagonists such as warfarin, that are frequently prescribed for the prevention of thromboembolic events in patients with atrial fibrillation (16), have been suggested to predispose to OA (17). Nonetheless, the direct effect of warfarin on human articular cartilage tissue homeostasis has not been assessed.…”
Section: Introductionmentioning
confidence: 99%